GENETIC TYPES OF METHANE FROM LAKE BAIKAL - Kalmychkov G.V.; Kuz'min M.I.; Egorov A.V.; Khlystov O.M. (My University, 2006)
In the coastal (shallow-water) part of Lake Baikal, we studied gas from several ice holes, which represent polynyas (ice-free water areas) typically formed at the end of March–beginning of April due to intense gas release from the lake floor. The water depth here is no more than 30–40 m. Gas seeps in the deep-water part of Baikal have been studied since the 1990s after the detection of seismoacoustic traces of gas seeps from the lake floor. Complex geophysical works in the Southern depression of the lake at a depth of ~1400 m revealed several morphologically distinct uplifts up to 40 m high and 800 m across with gas conduits and high heat flow.
Keywords: Baikal; methane